1965
DOI: 10.1139/v65-208
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Scf–lcao–mo Treatment of Thiophene, Furan, and Pyrrole

Abstract: The semiempirical SCF-LCAO-MO method of Pariser-Parr-Pople is utilized in the study of the a-electronic structures of thiophene, furan, and pyrrole. T h e core Hamiltonian expansion contains a Uz++ term, the potential due t o the ionized hetero-atom contributing two electrons to the a-system. The y z z , one-center coulomb repulsion integral for the hetero-atom is evaluated from the experimental spectroscopic data only. With the resonance integral pczc a s the only variable parameter, the calculated a*-a elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1968
1968
2006
2006

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In terms of electron density and free valence number, the enhanced reactivity of the thienyl substituent over that of phenyl can be viewed, rather naively, as a reflection of the fact that only five atoms are sharing the π-electrons of the aromatic sextet and quantitative yields of reaction are often observed, as in the case of the transformation of 1,2-bis(thiophene-2-yl)ethene into thieno[3,2- e ]benzo[ b ]thiophene …”
Section: Discussionmentioning
confidence: 99%
“…In terms of electron density and free valence number, the enhanced reactivity of the thienyl substituent over that of phenyl can be viewed, rather naively, as a reflection of the fact that only five atoms are sharing the π-electrons of the aromatic sextet and quantitative yields of reaction are often observed, as in the case of the transformation of 1,2-bis(thiophene-2-yl)ethene into thieno[3,2- e ]benzo[ b ]thiophene …”
Section: Discussionmentioning
confidence: 99%
“…A modified Pople-Pariser-Parr procedure has also been successfully applied to the calculation of the electronic spectra of 2-and 3-nitropyrrole. The first procedure, developed by ( 8 4 ) Brown (81) Lykos (85) Dahl ( 8 6 ) Julg (87) Leroy (88) Solony (89) Chiorboli (80) Evleth (91) Flurry (92) Kunii (93) Adams ( 8 3 ) Bloor (77) Zahradnik (94) DelRe (95) Allinger (96 > Aussems (97) p u j 0 l(98, Hirota ( DelRe, treats the σ-bonds as localized bonds. The first procedure, developed by ( 8 4 ) Brown (81) Lykos (85) Dahl ( 8 6 ) Julg (87) Leroy (88) Solony (89) Chiorboli (80) Evleth (91) Flurry (92) Kunii (93) Adams ( 8 3 ) Bloor (77) Zahradnik (94) DelRe (95) Allinger (96 > Aussems (97) p u j 0 l(98, Hirota ( DelRe, treats the σ-bonds as localized bonds.…”
Section: Scf π-Electron Calculationsmentioning
confidence: 99%
“…29 Semi-empirical calculations have not been able to provide a clear picture of the electronic spectrum. [30][31][32][33][34] While theoretical studies on thiophene molecule reported are based on ab initio quantum chemical approach, [35][36][37] due to its large size, similar studies on PT is difficult using these methods. Restricted configuration interaction (CI) technique is also not useful for solving these interacting systems as we need to extrapolate the results to the polymer limit and restricted CI calculation are not size consistent.…”
Section: Introductionmentioning
confidence: 99%